2015
DOI: 10.1108/el-05-2012-0045
|View full text |Cite
|
Sign up to set email alerts
|

Reading experiences influencing the acceptance of e-book devices

Abstract: Purpose – This paper aims to explore users’ perception of, and then intention toward using, e-book devices as new reading devices, based upon an integrated technology acceptance model (TAM), reading engagement based upon flow theory and readability. The recent introduction of e-book devices has drastically changed the way people access and use reading content. However, few studies have explored the impact of reading experience on acceptance of e-book devices. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 52 publications
1
18
0
3
Order By: Relevance
“…Aharony [12] conducted an empirical study to confirm that perceived usefulness, perceived ease of use, personal innovativeness and other personal characteristics are predictors of behavioral intention to use e-books. A further paper by Park, Sung and Cho [13] showed that "user acceptance of e-book devices was affected by hardware characteristics such as perceived mobility and viewing experience through the perceived ease of use and perceived usefulness." The authors explored user intention toward e-book devices as new devices, integrating reading engagement based on flow theory and readability constructs along with TAM.…”
Section: Related E-book Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Aharony [12] conducted an empirical study to confirm that perceived usefulness, perceived ease of use, personal innovativeness and other personal characteristics are predictors of behavioral intention to use e-books. A further paper by Park, Sung and Cho [13] showed that "user acceptance of e-book devices was affected by hardware characteristics such as perceived mobility and viewing experience through the perceived ease of use and perceived usefulness." The authors explored user intention toward e-book devices as new devices, integrating reading engagement based on flow theory and readability constructs along with TAM.…”
Section: Related E-book Literaturementioning
confidence: 99%
“…In addition to TAM theory, Park et al [13] applied flow theory; Lai and Chang [14], Lai and Ulhas [15] and Lee, Han, Lee and Lee [20] applied diffusion of innovation; Williams, Slade and Dwivedi [21] applied subjective norms; and Antón, Camarero and Rodríguez [22] used hedonic perspective and self-congruence theory to study adoption of e-books. Furthermore, Stone and Baker-Eveleth [23] applied the expectation-confirmation model to examine university students' intentions to use e-textbooks.…”
Section: Related E-book Literaturementioning
confidence: 99%
“…Ta dva primjera pokazuju da je kod tehnološkog aspekta osim korisnosti i praktičnost karakteristika koju prilikom ispitivanja percepcije treba uzeti u obzir kao nezavisnu karakteristiku. Park, Sung i Cho (2015) u okviru istog modela testiraju utjecaj doživljaja čitanja, odnosno utjecaj sadržaja na prihvaćanje e-čitača i pronalaze da je zadovoljstvo tekstom značajan faktor u prihvaćanju e-čitača. Drugim riječima, sadržajni aspekt ima utjecaj na tehnološki, pa prema tome nije svejedno što se čita.…”
Section: Uvodunclassified
“…Stupanj slaganja s tvrdnjama mjeren je na petstupanjskoj skali Likertovog tipa od "Uopće se ne slažem" do "U potpunosti se slažem". Istraživanja koja nalazimo u literaturi uglavnom obuhvaćaju problematiku korisnosti i praktičnosti (Chiang i Chen 2014, Lai i Ulhas 2012, Shin 2011, Jung et al 2012, odnosno doživljaja čitanja (Benedetto et al 2013, Park, Sung, i Cho 2015. Uz te dvije potencijalne latentne dimenzije dodali smo još i problem dostupnosti kao specifičan za Hrvatsku i slabo razvijeno tržište e-knjige, tako da su tvrdnje inicijalno u upitniku okupljene oko četiri predviđene latentne dimenzije: korisnost (6 tvrdnji), praktičnost (5 tvrdnji), doživljaj čitanja (5 tvrdnji) i dostupnost (5 tvrdnji).…”
Section: Slika 7 Kada Bi Mogli Birati Između Tiskane I E-knjige šTounclassified
“…Evaluating the quality of learning environments has a long tradition in educational technology and many qualitative and quantitative methods such as interview, focus groups and questionnaires have been developed. Most of these instruments were developed to fit existing theories about factors that predict achievement and to investigate which factors in the learning environment predict behavioural intention (51)(52)(53)(54)(55). Despite of pupils' development is considered in both strands of research, insights from research on the development of professional expertise have not yet been systematically implemented in instruments used for evaluating the quality of learning environments.…”
Section: Introductionmentioning
confidence: 99%